Envelhecimento, sexualidade e gênero: percepção de mulheres idosas no contexto urbano - Roubuste, Leandro da Silva (2024)
The themes of aging, sexuality and gender are the discussion proposal of this research. To do this, we initially need to highlight the important reality of the Brazilian and global population, which is the growing number of elderly people. The objective of the research is to understand the perception of elderly women living in the urban context regarding aging, gender and sexuality. For this, a field research strategy with a qualitative approach was used, selected to obtain information about the factors that can contribute and influence the application of a structured questionnaire in the eastern region of the city of Santa Maria-RS. The population sample was elderly women, members of the “Mulheres que Falam” group, located in the eastern region, characterized as urban, of the city of Santa Maria, RS. The instrument for carrying out the research was individual semi-structured narrative interviews with the women participating in the group. To collect data, the researcher attended the community group meetings where the project was publicized, as well as its objectives during the meetings, inviting the elderly women to participate.